Recovery of ammonia nitrogen from simulated reject water by bipolar membrane electrodialysis - Zhu, Ming (Environmental technology, 2024)
Ammonia monohydrate (NH3·H2O) is an important chemical widely used in industrial, agricultural, and pharmaceutical fields. Reject water is used as the raw material in self-built bipolar membrane electrodialysis (BMED) to produce NH3·H2O. The effects of electrode materials, membrane stack structure, and operating conditions (current density, initial concentrations of the reject water, and initial volume ratio) on the BMED process were investigated, and the economic costs were analyzed. The results showed that compared with graphite electrodes, ruthenium-iridium-titanium electrodes as electrode plates for BMED could increase current efficiency (25%) and reduce energy consumption (26%). Compared with two-compartment BMED, three-compartment BMED had a higher ammonia nitrogen conversion rate (86.6%) and lower energy consumption (3.5 kW· h/kg). Higher current density (15 mA/cm2) could achieve better current efficiency (79%). The BMED performances were improved when the initial NH4+ concentrations of the reject water increased from 500 mg NH4+/L to 1000 mg NH4+/L, but the performance decreased as the concentration increased from 1000 mg NH4+/L to 1500 mg NH4+/L. High initial volume ratio of the salt compartment and product compartment was beneficial for reducing energy consumption. Under the optimal operating conditions, only 0.13 $/kg reject water was needed to eliminate the environmental impact of reject water accumulation. This work indicates that BMED can not only achieve desalination of reject water, but also generate products that alleviate the operational pressure of factories